Morphological Influence of Polypyrrole Nanoparticles on the Performance of Dye–Sensitized Solar Cells. (10th February 2015) - Chang, Ling-Yu; Li, Chun-Ting; Li, Yu-Yan; Lee, Chuan-Pei; Yeh, Min-Hsin; Ho, Kuo-Chuan; Lin, Jiang-Jen
Graphical abstract: Various polypyrrole (PPy) morphologies with irregular sheet, hierarchical nanosphere, and nanosphere were synthesized using the commercial surfactants and home–made polymer, and used as the counter electrode in dye–sensitized solar cells. The excellent electrocatalytic ability of hierarchical nanosphere PPy was attributed to its high surface area, as determined by a rotating disk electrode. Highlights: Polypyrrole (PPy) with various morphologies were synthesized by oxidative method. PPy was used as the counter electrode (CE) in dye–sensitized solar cells (DSSCs). PPy with irregular sheet, hierarchical nanosphere, and nanosphere were obtained. Hierarchical PPy CE gave the best catalytic ability due to it high surface area. The DSSC with hierarchical PPy CE achieved the best cell efficiency of 6.71%. Abstract: Polypyrrole (PPy) with various morphologies were synthesized by chemical oxidative polymerization and further used as the counter electrode (CE) in dye–sensitized solar cells (DSSCs). The conventional anionic surfactant, docusate sodium salt (AOT), cationic surfactant, cetylmethyl ammonium bromide (CTAB), and the newly developed polymeric dispersant, poly(oxyethylene)–imide (POEM), were employed in the PPy synthesis. Scanning electron microscopy images (SEM) revealed diversified morphologies of the synthesized PPy nanoparticles with irregular sheet (IS), hierarchical nanosphere (HNS), and nanosphere (NS), corresponded to the choice of the commercial surfactants AOT and CTAB, as well as the home–made POEM, respectively. Fourier transform spectroscopy (FT–IR) and X–ray diffraction (XRD) analysis were used to confirm the PPy structures and crystalline properties. When fabricated into films and used as CE in DSSCs, the PPy–HNS demonstrated the superior cell efficiency of 6.71 ± 0.16% to those of PPy–IS (5.46 ± 0.31) and PPy–NS (6.31 ± 0.24), respectively. The excellent electrocatalytic ability of PPy–HNS was essentially attributed to its high electrochemical surface area ( A e ), which was quantitatively calculated through a rotating disk electrode system by using the Koutecky–Levich equation. Brunauer–Emmett–Teller (BET) surface area measurement, electrochemical impedance spectroscopy (EIS), and cyclic voltammetry (CV) were also used to substantiate the explanation for the DSSC performances.